2019
DOI: 10.1101/569129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved CUT&RUN chromatin profiling and analysis tools

Abstract: We previously described a novel alternative to Chromatin Immunoprecipitation, Cleavage Under Targets & Release Using Nuclease (CUT&RUN), in which unfixed permeabilized cells are incubated with antibody, followed by binding of a Protein A-Micrococcal Nuclease (pA/MNase) fusion protein (1). Upon activation of tethered MNase, the bound complex is excised and released into the supernatant for DNA extraction and sequencing. Here we introduce four enhancements to CUT&RUN: 1) a hybrid Protein A-Protein G-MNase constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 54 publications
(70 reference statements)
0
33
0
Order By: Relevance
“…We used sparse enrichment analysis for CUT and RUN (SEACR) (Meers et al, 2019) to call enriched regions from all 65 factor-time point combinations and identified the 26 most informative combinations, meeting a threshold of at least 4,000 peaks called. As expected, binding of pluripotency factors such as Oct4, Sox2, and Nanog was confined largely to H1 cells, whereas ''intermediate '' regulators,, were most enriched between day 2 and day 4, and DE-specific regulators such as Sox17 and FoxA1/FoxA2 were most enriched at days 4 and 5 (Figure 1B).…”
Section: Temporal Chromatin Profiling Identifies Stage-specific Multifactor Binding Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…We used sparse enrichment analysis for CUT and RUN (SEACR) (Meers et al, 2019) to call enriched regions from all 65 factor-time point combinations and identified the 26 most informative combinations, meeting a threshold of at least 4,000 peaks called. As expected, binding of pluripotency factors such as Oct4, Sox2, and Nanog was confined largely to H1 cells, whereas ''intermediate '' regulators,, were most enriched between day 2 and day 4, and DE-specific regulators such as Sox17 and FoxA1/FoxA2 were most enriched at days 4 and 5 (Figure 1B).…”
Section: Temporal Chromatin Profiling Identifies Stage-specific Multifactor Binding Modulesmentioning
confidence: 99%
“…EChO was implemented as follows: 1) We combined all replicates for each factor-time point combination to maximize the number of fragments used in size calculations. 2) For each SEACR (Meers et al, 2019) peak detected in a CUT&RUN dataset, we found all CUT&RUN fragments from the same dataset that overlapped it using bedtools intersect with the ''-wao'' flag (Quinlan and Hall, 2010). 3) For every fragment overlapping the peak in question, we calculated the distance of the center of the fragment from the center of the peak (with negative values corresponding to upstream and positive to downstream), and paired it with the fragment size in bp to produce a table of positions versus sizes.…”
Section: Echo Software and Implementationmentioning
confidence: 99%
“…RNA-seq analyses at EB day 2 revealed that $60% of differentially expressed genes were downregulated in Wdr5 KO EBs (Figure 4A). We used CUT&RUN (cleavage under targets and release using nuclease sequencing) to define the genomic tar-gets of WDR5 and H3K4me3 in WT and Wdr5 KO EBs at day 2 (Figure 4B) (Meers et al, 2019). H3K4me3 at WT WDR5-bound chromatin targets were reduced in Wdr5 KO EBs (Figure 4C).…”
Section: Wdr5 Regulates Target Gene Expression With Dynamicmentioning
confidence: 99%
“…luciferase reporter assays, chromatin immunoprecipitation (ChIP), electrophoretic mobility shift assays (EMSAs), in utero electroporation (IUE) studies; as well as as well as more recently reported screening methods (e.g. multi‐plex reporter assays (MPRAs) (Mulvey, Lagunas, & Dougherty, 2021), mammalian targeted damID (MaTaDa) (Cheetham et al, 2018), Cut&Run (Meers, Bryson, Henikoff, & Henikoff, 2019)) and, where feasible, binding free energy calculations (Blake et al, 2021; Hemming et al, 2019; Hemming et al, 2020)) in order to study the DNA‐binding, protein–protein interaction and transcriptional regulatory signalling properties of TFs as well as their query variants (Table 3). It is noteworthy that MPRAs, MaTaDa and Cut&Run leverage advances of recent years in massively parallel sequencing technologies and robotic screening platforms to make them exciting new functional screening approaches to map causal missense TF variants in health and disease.…”
Section: Discussionmentioning
confidence: 99%